Our members be unlimited : a comic about workers & their unions - Wallman, Sam (Scribe Publications, 2022)
In our current political climate, people are looking for answers - and alternatives. The promise of unions is that their 'members be unlimited': that they don't belong to the rich, the powerful, or special interests, but to all workers. How did the idea of unionism arise? Where has it flourished? And what are its challenges in the 21st century? From Britain to Bangladesh, from the first union of the 18th century to today, from solidarity in Walmart China to his own experiences in an Amazon warehouse in Melbourne, comics journalist Sam Wallman explores the urge to come together and cooperate that arises again and again in workers and workplaces everywhere.